Análise da relação chuva-vazão na bacia hidrográfica do Rio Paranaíba, Brasil - Maciel, Samuel Alves (2017)
The main objective of this research was to analyse the association between rainfall and runoff variables in the Paranaíba River Basin which comprehends some areas of the states of Goiás - (GO), Minas Gerais - (MG), Mato Grosso do Sul - (MS) e do Distrito Federal - (DF), Brazil. The study basin is located in the Paraná Hydrographic Region, comprising part of the Midwest and Southeast regions and covering a drainage area of 223.000 km². For the purpose of this research, daily pluviometric and fluviometric data were obtained from the Brazilian Government National Water Agency (ANA) of 52 stations, 26 for each variable, based on a 38 year series (from 1975 to 2012). After tabulating the data, the following methodologies contributed to the understanding of the relationship between rainfall-runoff: preliminary statistical data, coefficient of variation, determination of specific flows, The Standardized Precipitation Index (SPI), rainfall charts and stage hydrographs, dispersion graphs, Pearson Linear Correlation between both variables and Decomposition of Series for trend analysis. The results indicate an annual average of precipitation of 1.468,4 mm in a seasonal regime from October to March (rainy season) and from April to September (dry season). The runoff regime accompanies the rainfall, presenting during the rainy season, an increase in the mean values from 28,4 m³/s in October to 88,1 m³/s in March and a decrease within the dry season from 69,6 m³/s in April to 24,6 m³/s in September. For all the stations, the peaks and low rainfall focused directly on the runoff regime and it should be considered the delay period in the increase of the runoff in relation to the beginning of the rain. With regard to the correlation between rainfall and runoff variables, it was positive and strong, which shows that the higher the total amount of rainfall is, the greater the runoff is. The trend analysis using the Decomposition of Series presented a runoff reduction trend of 42,3% of the stations, an increase of 34,6% of them, firstly 15,4% of reduction and next of increase and initially7,7% of increase and then a reduction of the fluviometric regime.